Islamic Law and Indonesia’s New Criminal Code: a Critical Analysis Based on Maqāṣid Al-Sharī‘ah - Ahmad Badrut Tamam; Moh. Aqil Musthofa; Moh. Sahlul Khuluq (MADINAH, 2026)
Indonesia's New Criminal Code (Law Number 1 of 2023) has reignited debates that criminal law scholars and civil society have long been circling, where exactly does the state's reach into private conduct end, and what legitimizes that reach in the first place. The provisions on presidential insult (Articles 218–220) and sexual morality, adultery and cohabitation outside marriage (Articles 411–412), have attracted the sharpest criticism, not just from human rights advocates but from practitioners who know how vague criminal provisions behave in politically sensitive environments. This article runs those provisions through maqāṣid al-sharī'ah, not as theological endorsement or refutation, but as a proportionality framework with genuine teeth. The approach is normative and doctrinal. What the analysis consistently finds is that the contested provisions criminalize conduct without adequately showing what harm they prevent, a gap that maqāṣid theory does not overlook, and that criminal law doctrine cannot responsibly ignore.